Three new diatom species of the genus Diploneis (Bacillariophyta) from Lake Baikal. Issue 2 (3rd April 2019) - Rodionova, Yelena; Pomazkina, Galina; Sherbakova, Tatyana
Abstract : We present three new species, Diploneis implicatus, Diploneis lacustris and Diploneis pumicosus, from the littoral zone of Lake Baikal. Descriptions of these species are based on light and scanning electron microscopical features that distinguish them from other taxa. Diploneis implicatus exhibits external openings of each stria areola flanked by short siliceous thickenings of the vimenes and virgae forming a regular pattern on the external valve that is unique for the genus. Similar structures have previously been reported only in the distantly related and ecologically different Craticula citroides . Diploneis lacustris possesses a conopeum, uncommon in Diploneis and known only in Diploneis aokiensis from Japan. In our species, the conopeum is variable in structure and only developed in the apical quarter of the valve. The third species, Diploneis pumicosus, has a distinctive raphe system morphology similar to that in the single valve of Diploneis conopeospongiosa from Lake Baikal. All three species inhabit silty bottom habitats at depth of 20 m or more, and have so far been found in the southern basin of Lake Baikal. The diversity of Diploneis species in Lake Baikal is a rich resource for further understanding the genus.